Potential of Curcumin in Turmeric as a Preventive Modality from Covid-19 in Pregnant Women - Fayola Issalillah (metromedia.education, 2021)
Coronavirus disease 2019 (Covid-19) is a state of health emergency and global concern. Unfortunately, there is no effective therapeutic strategy available in dealing with Covid-19 infection. This can endanger risk groups, especially pregnant women. Various studies are competing to develop the therapeutic potential of Covid-19 from herbal compounds, one of which is curcumin. This study aims to determine the potential of curcumin in turmeric as a preventive modality from Covid-19 in pregnant women. This paper uses literature study. Based on the results obtained, the anti-viral, anti-inflammatory, anti-oxidant and anti-coagulant effects in curcumin play an important role in preventing the development of the SARS-CoV-2 virus in humans based on various mechanisms. Low doses of curcumin have also been proven safe for consumption by pregnant women. Therefore, routine and low-dose curcumin supplementation can prevent Covid-19 infection in pregnant women.